Daisy Trail Cycle. Issue 1 (2nd January 2016) - Goodey, Dave
Abstract : Dave Goodey's wife Emma died in 2013. Two years later Dave decided to take on a challenge in her memory – he would ride across Europe on a tandem bicyle raising funds for several charities which had meant something to himself and Emma. In this article he reﬂects on his journey, which became both a tribute to Emma and a symbol of the struggles he faced as he journeyed through grief.